The role of nursing in the care of patients with pain due to endometrios: a literature review (Research, Society and Development, 2021)
This study intends to describe the role of nursing in the reception of patients who present pain due to endometriosis, from the diagnosis, early or late, to the treatment. Thus, it is necessary to explain the pathology and its physical and psychological consequences, as well as its incidence in women today, so that nurses can be updated to promote a dignified treatment to the patient. It is important to emphasize that the nurse is the key to obtaining a good result in the development of the treatment, emotionally supporting the woman with the pathology and offering professional support. The methodology used to present the theme was a literature review, using books, dissertations, scientific articles, theses and journals, by searching Google Scholar, with the terms endometriosis, its causes, pathogenesis, possible treatments and nursing action, published from 2014 to 2021. The study was divided into two sections, in order to explain the pathology and its possible causes, followed by the role of nursing for patients diagnosed with endometriosis. Considering the aggressiveness of endometriosis and the lack of correct information about it in society, which causes late diagnosis, the nursing team's role in welcoming the patient is extremely important, from the first complaint of symptoms to the post-diagnosis, considering that the sequelae of the disease are both physical and emotional.